(untitled) (Medical Forum Monthly, 2024)
Objective: To study the cytological pattern of disease in females presenting with breast lumps/ swellings. Study Design: A retrospective / descriptive study Place and Duration of Study: This study was conducted at the Pathology Department, Nawaz Sharif Medical College, University of Gujrat from Jan 2015 to Dec 2017. Materials and Methods: It consisted of 1046 patients having 1085 breast lumps/ swellings. Sampling was done in Aziz Bhatti Shaheed Teaching Hospital and a private hospital in Gujrat. The records of all the patients were retrieved, compiled and analyzed with respect to the types of pathology, age and various diagnostic entities. Results: We analyzed 1085 breast lesions. More lesions were seen on left side (53.6%). Mean age of patients was 39.07 years. Most patients presented in fourth decade (27.2%), followed by third decade (24.9%). We divided the lesions into five main categories. Benign category (C2) was the largest with 56.8% of the lesions. It was followed by the malignant category (C5%) with 33.5% of the patients. The C3 and C4 categories contained 4.7% of the lesions each. C1 category contained only 0.3% of the lesions. Fibroadenoma was the commonest lesion in the benign neoplastic group. Inflammatory lesions were commonest lesion in the benign non-neoplastic group. Ductal carcinoma was the most prominent lesion in the malignant category with 69% of the cases. Conclusion: Our findings of benign lesions being the commonest and malignant second to them is in conformity with most other studies. There are variations in the frequencies of various categories of lesions and age incidences in literature.